Locally D-optimal Designs for Exponential Regression - Weng Kee Wong; Viatcheslav B. Melas; Holger Dette (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
We study locally D-optimal designs for some exponential models that are frequently used in the biological sciences. The model can be written as an algebraic sum of two or three exponential terms. We show that approximate locally D-optimal designs are supported at a minimal number of points and construct these designs numerically.
Keywords: 519; Regression; Modell-Spezifikation; Theorie